A SIMPLE AND RAPID METHOD FOR SIMULTANEOUS ESTIMATION OF GLYCYRRHETINIC ACID AND PIPERINE BY HPTLC IN A HERBOMINERAL FORMULATION - Ashish Trivedi; S. H. Mishra (Wolters Kluwer Medknow Publications, 2010)
Many of the traditional herbal formulations contain extracts of Piper longum and Glycyrrhiza glabra, piperine and glycyrrhetinic acid respectively, being active constituents of these two herbs. An attempt has been made to develop a simple, precise, rapid, and cost-effective high-performance thin-layer chromatographic (HPTLC) method for simultaneous estimation of these in a herbomineral formulation (Efiplus® Capsules). Precoated silica gel 60 F254 plates with toluene-ethyl acetate-glacial acetic acid 12.5:7.5:0.5, as mobile phase were used in chromatographic determinations. The plates were scanned and the compounds were quantified at their wavelengths of maximum absorption of 260 and 331 nm for glycyrrhetinic acid and piperine respectively. The respective RF values of glycyrrhetinic acid and piperine were 0.51 and 0.55. Under these experimental conditions linearity was observed between 0.8-2.6 µg/spot for glycyrrhetinic acid and between 10-50 ng/spot for piperine and average recovery was 96.25% for glycyrrhetinic acid and 98.55% for piperine.